Characterisation of rainfall rate and rain attenuation at Ku-band for earth-space communication - Zhu, Chun Ning. (2009)
Based on the need for a critical assessment of the impact of rain on the operation of Ku-band satellite services in Singapore, studies have been done to characterise rainfall rate and rain attenuation at Ku-band.